Grounding maladaptation: Agricultural change as a source of climatic risks in small farms of the Mixteca Alta, Mexico. Issue 127 (December 2021) - Dobler-Morales, Carlos; Álvarez Larrain, Alina; Orozco-Ramírez, Quetzalcóatl; Bocco, Gerardo
Highlights: Studies of small farm adaptation to climate change often focus on positive results. To remedy this bias we study maladaptive farming practices in rural Mexico. We find farmers often introduce new sensitivities and increase rigidity on the farm. Maladaptation is often involuntary, driven by adverse economic conditions to farming. A focus on maladaptation reveals constraints on capacities and motivations to adapt. Abstract: There is extensive research on smallholder farmers' strategies to minimize the effects of extreme weather on their production. This research has proved crucial in revealing opportunities to adapt small farms to future climate change. However, it is common for this type of work to focus exclusively on successful strategies, framing adaptation as always positive, and thus missing the broader range of farmers' cultivation practices and the factors that shape them. In this paper we ask: what can be revealed by examining practices that elevate —rather than reduce—the risk of crop failure amid unfavorable weather? This question is explored through an empirical case study of the Mixteca Alta, in southern Mexico, where the climate is becoming increasingly hostile to farming. Based on a qualitative research approach, we analyze whether and how a higher incidence of crop failure may be explained by changes in the way farmers cultivate, and why farmers may neglect the climatic risks that those changes entail. Our study finds that current management of cropping systems in the Mixteca has substituted resilient with sensitive components, and rendered these systems more rigid overall against erratic weather conditions. Adverse market and institutional conditions to farm and an accompanying process of livelihood diversification were identified as underlying drivers of the adoption of maladaptive agricultural practices. Our findings thus ascribe maladaptation to the trade-offs that smallholders must negotiate when confronted with multiple threats to their livelihoods. Identifying these trade-offs is key to informing policy and practice on how to enhance resiliency of cropping systems against climate change.